The Beauty of traditional Korean arts - Kim, Dong-ok; Cha, Hye-mi; Jeong, Hye-won (Korean arts & lifestyle, 2005)
Provides an overview of traditional Korean arts, including painting, ceramics, music, and dance. Describes different styles of Korean pottery and introduces a variety of traditional musical instruments. Presents pansori, a traditional style of reciting dramatic songs. Describes various types of folk dancing, including salpuri, a dance derived from Shamanistic exorcism rituals, the Hahoe mask dance drama, and seungmu, or Buddhist monks' dance.